Gardening in summer-dry climates : plants for a lush, water-conscious landscapes - Harlow, Nora (Timber Press, Inc., 2020)
A landscape architect provides detailed information for gardeners looking to plant and maintain a lush and colorful garden that can flourish in summer droughts and wet winters and includes an A-Z list of appropriate plants.